2016
DOI: 10.1103/physreva.93.062318
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and nonclassicality: A mutual impression

Abstract: We find a sufficient condition to imprint the single-mode bosonic phase-space nonclassicality onto a bipartite state as modal entanglement and vice versa using an arbitrary beam splitter. Surprisingly, the entanglement produced or detected in this way depends only on the nonclassicality of the marginal input or output states, regardless of their purity and separability. In this way, our result provides a sufficient condition for generating entangled states of arbitrary high temperature and arbitrary large numb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…pointed that efficient quantum computation is possible to be realized by using only beam-splitters, phase shifters, single photon sources and photo-detectors35. Although beam-splitters are linear optical devices, they can generate quantum entanglement36373839.…”
mentioning
confidence: 99%
“…pointed that efficient quantum computation is possible to be realized by using only beam-splitters, phase shifters, single photon sources and photo-detectors35. Although beam-splitters are linear optical devices, they can generate quantum entanglement36373839.…”
mentioning
confidence: 99%
“…On the other hand, however, quantum correlations in quantum optics lack such a nonlocal operational justification, i.e., there is no particular quantum information protocol which exploits phase-space nonclassicality to outperform a classical counterpart protocol. Although, it has been recently shown that such nonclassicalities provide either necessary or sufficient resources for entanglement generation [11][12][13], which then can be used in various protocols.…”
mentioning
confidence: 99%
“…Indeed many strategies can be taken to implement SEW depending on M A and M B , while taking care that the obtained witness contains an entangled eigenspace [8,9]. To show that this is not a requirement of UEW, we give the following simple-to-construct example of a UEW strategy to detect a range of entangled states.…”
mentioning
confidence: 99%
“…This simplification, however, comes at a cost: first, different entangled states in general require different EWs to be detected; second, not every EW can be practically realized, i.e., can be decomposed into operators corresponding to available local measurement devices (See also Refs. [7][8][9] for examples of the reverse procedure: constructing EWs from local observables); third, when such a decomposition is possible, it might require multiple measurement devices (with multiple settings) to be implemented; and fourth, witnessing bounds can be elusive in the presence of experimental imperfections. Consequently, the goal is to construct EWs that have a simple decomposition and, at the same time, detect a large set of entangled states.…”
mentioning
confidence: 99%